PENGAWASAN PEMERINTAH DAERAH KOTA PEKANBARU TERHADAP PENGECER BAHAN BAKAR MINYAK BERSUBSIDI TAHUN 2011 – 2012 - Pintorhot, Panca Saut; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to identify and analyze the implementation of Pekanbaru city government supervision in order to cope with the rise of the presence of persons who are not responsible for the trade in subsidized fuel oil in the year 2011 to 2012. Problem in this study is not optimal surveillance conducted by the State Government Department of Industry and Commerce as vastness of space coverageThis study found the first implementation of the supervision by the Department of Industry and Trade is less visible is the rise of subsidized fuel retailers. Both retailers of subsidized fuel does not pay attention to the safety aspect when - time may threaten the safety of the people. Third-party retail outlets is still a lack of socialization (General Fuel Filling Station) in the procedures and rules set together - together with the government. Fourth is still a lack of cooperation between the Department of Industry and Trade, Police, pegelola gas station (Fuel Filling Stations General), the public and other parties to minimize the widespread circulation of subsidized fuel retail.Keywords: Monitoring, the role of government to fuel the rise of retailers